A Comprehensive Literature Review on the Factors Influencing Resistance to Organizational Change and Strategies for Effective Management - Suyuthi, Nurmadhani Fitri; Amaliah, Amaliah; Linggi, Tiara Titania (Scieclouds Publishing, 2025)
A typical organizational change management issue is organizationalresistance to change. This paper looks at literature on sources of resistance basing it on individual, group and organizational factors. At individual level, the following variables were found to be the reasons for resistance; perceived risk by not knowing what to expect next in the course of implementing change, insecurity of their jobs, and perceived that leaders cannot be trusted. Other factors include: The interaction between people in as group since this leads to peer pressure and maintaining of standards that have been set, therefore leading to resistance of change. Institutional factors such as ineffective communication, inadequate resources and rather more set organizational culture also contributeto resistance. The recommendations are derived from a review of the coping strategies with clear directions of invoking communication, engaging the employees, leadership involvement, and procuring more competent training and support. Lacking proper attention to the concerns and requirement of the employees at the workplace can be the major hurdle in the path of proper implementation of change management. Indeed, the outcomes show that resistance cannot be regarded as an only negative factor, but it is the possibility to discuss and develop. By adopting and applying all these points, an organization can therefore learn how to manage change and embed change in order to bring about the Right Change successfully and sustainably.